2016
DOI: 10.1111/1758-5899.12331
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Burden of Out‐of‐Pocket Health Payments in Denmark, Germany and Poland

Abstract: It is important to monitor equity of access to health services in all countries. We assessed the levels of out-of-pocket (OOP) health spending in three European countries: Denmark, Germany and Poland. Using data from national databases (i.e., Statistics Denmark, German Socio-Economic Panel, and National Statistical Office of Poland) for the period 2000-2010, we applied common methods to assess the rate of households with 'catastrophic' OOP health spending and the concentration of health spending in income-orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Moreover, CHE in Portugal was disproportionately concentrated among the poorest while the opposite occurred in Greece. Zawada et al [23] derived concentration curves for CHE for three countries. Their results are not fully comparable with ours as they considered in their inequality analysis a threshold (defining CHE) equal to 10% of total income.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, CHE in Portugal was disproportionately concentrated among the poorest while the opposite occurred in Greece. Zawada et al [23] derived concentration curves for CHE for three countries. Their results are not fully comparable with ours as they considered in their inequality analysis a threshold (defining CHE) equal to 10% of total income.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the authors concluded that in Poland (year 2010) catastrophic OOP were concentrated among the poor, whereas in Denmark (year 2010) they were concentrated among the rich, while the disparities in Germany (year 2009) were variable, but close to the equality line. In Zawada et al [23], the country with greater inequality, Poland, also had the largest incidence of CHE and the country with less inequality, Germany, also had the lowest incidence of CHE. Although in a completely different setting (low income country), a study for Tajikistan [31], using the same method as in our work, found that the incidence of CHE decreased from 31% in 2008 to 18.8% in 2011, while the level of inequality was relatively low, with the CI evolving from 0.008 in 2008 to − 0.072 in 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while 0.3% of households in the present study are impoverished by OOPP when utilising the 60% of median income poverty line, prevalence is 1.4% in the highest of four World Bank income groups and 2.3% worldwide (World Health Organization and The World Bank, 2021). Even more so, prevalence of CHE when using the budget share approach and a 10% threshold is 0.5% in the current study, compared to 1.0% for Germany overall and 15.8% in the highest World Bank income group (Zawada et al ., 2017; World Health Organization and The World Bank, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed the increasing impact of moral hazard on health care expenditures, especially in health systems that work with fee-for-service payment models [14] , [15] and those without a mandatory referral system [16] , [17] . The presence of these two determinant factors and high medical insurance population coverage (about 95%) in Iran [18] , seems to have provided the appropriate conditions for the ex-post moral hazard problem.…”
Section: Introductionmentioning
confidence: 99%